2019
DOI: 10.7554/elife.48193
|View full text |Cite
|
Sign up to set email alerts
|

Repression of ferritin light chain translation by human eIF3

Abstract: A central problem in human biology remains the discovery of causal molecular links between mutations identified in genome-wide association studies (GWAS) and their corresponding disease traits. This challenge is magnified for variants residing in non-coding regions of the genome. Single-nucleotide polymorphisms (SNPs) in the 5ʹ untranslated region (5ʹ-UTR) of the ferritin light chain (FTL) gene that cause hyperferritinemia are reported to disrupt translation repression by altering iron regulatory protein (IRP)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The LOC100862446 gene is an ortholog of Ftl1 , so it would also be detected as Ftl1 . Recently, it has been shown that eIF3 acts as a repressor of Ftl1 translation in vitro 33 . Our results confirm the link between eIF3 and Ftl1 and, for the first time, provide evidence for the repression of Ftl1 translation by eIF3 in vivo in the liver.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The LOC100862446 gene is an ortholog of Ftl1 , so it would also be detected as Ftl1 . Recently, it has been shown that eIF3 acts as a repressor of Ftl1 translation in vitro 33 . Our results confirm the link between eIF3 and Ftl1 and, for the first time, provide evidence for the repression of Ftl1 translation by eIF3 in vivo in the liver.…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, 4 out of the 6 identified genes are involved in the iron metabolism pathway (light- and heavy-chain ferritins LOC100862446 , Ftl1 , and Fth1 and hepcidin Hamp2 ). Recent research provides an additional confirmation for the link between eIF3 and ferritin genes 33 . Previously, photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) analysis showed interaction between ferritin light-chain (FTL) mRNA and eIF3 subunits 16 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While eIF3 does not appear to bind to this element directly, removal of the motif strongly derepresses the translation of luciferase reporters in vitro and in vivo . Direct binding of eIF3 to a sequence motif in the 5′-UTR was recently implicated in translational suppression of the mRNA encoding ferritin light chain (FTL; Pulos-Holmes et al, 2019 ). The eIF3-binding motif contains two single nucleotide polymorphisms associated with hyperferritinemia.…”
Section: Eif3 and Translational Repressionmentioning
confidence: 99%
“…eIF3 plays a role in transcript-specific translation regulation [ 11 ], and eIF3 subunits bind directly to the HCV IRES element [ 12 , 13 , 14 ] and other secondary structures of mRNAs [ 15 ]. It is also involved in the repression of ferritin light chain translation [ 16 ]. Another binding partner of eIF3 is the RNA polymerase subunit hRPB11 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%